2013
DOI: 10.1002/elps.201200646
|View full text |Cite
|
Sign up to set email alerts
|

Capillary electrophoresis for monitoring bioprocesses

Abstract: Chemical characterization and monitoring of fermentation broths and cell culture media provide significant information on the changes occurring within these complex and dynamic systems. Analytical methods based on CE in capillaries and microchips are attractive for integration in instrumental tools to obtain this critical data, improving the understanding and control of bioprocesses. In this review, the use of CE for chemical characterization and monitoring fermentations is discussed, organized by analyte clas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 94 publications
0
12
0
Order By: Relevance
“…Heating/cooking and/or fermentation processes can modify the quantity of existing AAs and introduce new AAs in the product. The applicability of CE for bioprocess monitoring has also been demonstrated . Recently, Turkia et al.…”
Section: Amino Acids Biogenic Amines and Other Hazardous Aminesmentioning
confidence: 99%
“…Heating/cooking and/or fermentation processes can modify the quantity of existing AAs and introduce new AAs in the product. The applicability of CE for bioprocess monitoring has also been demonstrated . Recently, Turkia et al.…”
Section: Amino Acids Biogenic Amines and Other Hazardous Aminesmentioning
confidence: 99%
“…Conventionally, MP‐CE is used for concurrent analysis of the acid dissociation constant (p K a ) and log P determinations using 96 capillaries . Recently, MP‐CE was applied for monitoring of product formation in fermentation processes and single enzyme reactions .…”
Section: Introductionmentioning
confidence: 99%
“…For this last version of our synthesis of the CE work relating to AA in capillary electromigration methods, we observed the increase of metabolomic studies. Other review articles have reported on CE separation techniques, but are not dedicated to AA . One was focused on selenoamino acids and another on the use of microchip electrophoresis for AA ana‐lysis .…”
Section: Introductionmentioning
confidence: 99%